Authentication at Single-Point-of-Access in Cloud Environments (International Journal of Engineering and Computer Science, 2017)
Cloud computing is a rising innovation and increase consideration in scholastic and business range. Assets are pooled and offer with clients on interest. With a specific end goal to give better execution of cloud environment, undertaking planning is a paramount issue. The objective of the study to explore the different environments of the cloud infrastructure w.r.t security. It is big challenge for the cloud service provider company to implement the security and meeting the highest level of the service with the providing quality service and secure environments to the clients. This is how the Cloud service providing companies build the trust relationship with their clients. The propose model is the security optimization of the already implemented security in the cloud environments along with the quality service in terms of required bandwidth and required infrastructure like Saas, Paas, or Iaas. Meeting both, quality of service and security, Cloud service Provider Company has to do lot of working as the cloud has multiple integrated infrastructures. It will be a big loop hole if a cloud service provider company give access to their actual servers or live IPs to provide services to the clients. There will be lost of resources, time and availability of resources to the legitimate users. The primary objective of the study is to build a model which provides us un-authenticated and un-authorized users blocked from one single point which is other than the service provider to the clients of Saas, Paas, or Iaas and the resources to authenticate and authorize a user with in the cloud are used by the legitimate users.